(untitled) (LEARNing Landscapes, 2015)
In this interview, Megan Webster describes key tenets of teachers’ professional development. First, it needs to be practice-focused, meaning that the subject is very close to what teachers do every day. Secondly, teachers need to have opportunities to examine expert forms of practice; teachers need models of excellent performance. Finally, teachers must be able to practice and receive feedback in a supportive environment with peers who work in the same subject. This model, described as the "cycle of investigation and enactment," is best implemented in a sustained, long-term way. This model allows teachers to build relationships, develop trust, and commit to improving their teaching practice. She concludes by stating that high-quality professional development for teachers is "one of the greatest levers for change that we have."